Biofluid mechanics : an introduction to fluid mechanics, macrocirculation, and microcirculation /: an introduction to fluid mechanics, macrocirculation, and microcirculation. (2021) - Rubenstein, David A; (Assistant professor), Yin, Wei; Frame, Mary D
No abstract available